A Mobile Application for on-Demand Scheduling of Health Services - Quincozes, Vagner E.; Quincozes, Silvio E.; Kreutz, Diego; Mansilha, Rodrigo B.; Kazienko, Juliano F. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: The mass adoption of smartphones is reshaping the digital health market. Problem: Among the technological solutions for digital health exist those specifically for scheduling medical appointments. However, we observed that existing solutions are still professional-centric. Solution: In this work, we first (i) categorize existing scheduling models and then (ii) present a patient-centric mobile application. IS Theory: We use the Customer Focus Theory, taking into account customer satisfaction throughout the development and evaluation of our software. Method: We evaluate our solution using two known methods: (i) a self-assessment using the UXUG-AP technique and (ii) quantitative research using a questionnaire based on the well-known TAM indicators and sentences. Summary results: Our application complies with 84% of the items in the UXUP-AP technique. The usability survey results show that 68.6% of participants consider MedBe easy to use and, 62.9% disagree that using MedBe requires a lot of mental effort. Contribution and impact in the IS area: The main contributions are: (i) categorization of scheduling types, (ii) a mobile application that implements Scheduling 4.0, (iii) user experience evaluation, and (iv) application usability evaluation.